The role of value chain activities in enhancing competitive response: An analytical study of the opinions of a sample of managers in cement brick production plants in Sulaymaniyah Governorate - مەحمود, عوسمان کەریم (Sulaimani Journal for Humanities, 2020)
The aim of this study is to investigate the role of value chain activities of both types (activities). infrastructure, support activities) in strengthening and external competitiveness in its dimensions (speed, stability). and consistency, efficiency) by analyzing the opinions of a number of managers and their colleagues in factories Construction of cement blocks in Sulaimani province. The research takes an analytical approach and answering the questions raised in the research problem, by sharing the opinions of a number of people Managers and assistants in cement block production factories in Sulaimani province. His assumptions The research was organized according to its objectives. 44 survey forms were distributed to managers, officers and presidents Sections of cement block factories in a community of 50 people Confidence level (95%), margin of error (5%), a total of 43 forms were returned, of which 42 were suitable for analysis One form was removed, and a number of statistical methods were used to prove the truth of its assumptions Research, as a statistical center, measurement deviation, difference factors, rates of occurrence and combinations Simple and multiple linear leakage. The results of the analysis proved his hypotheses and were then made possible in their light Several conclusions can be drawn, the most important of which is the attention of the research factories to the dimensions of their activities Supply chain is the central level, while understanding the dimensions of external competition in the factory It is low in research, and basic activities and supports are also related With external competition, they have different effects on external competition in the studied factories. This is in addition to making a number of recommendations, the most important of which is that the research factories should pay attention to complete the dimensions and external competitiveness and supply chain analysis in order to strengthen and external competition, in order to achieve its objectives in terms of improving its competitive position and meaning in in the market continuously
Keywords: Sulaymaniyah governorate; Value chain; Primary activities; supportive activities; competitive responsiveness; Cement block factories